Autism in the media: A longitudinal study of stigma cues and framing of attribution. (December 2020) - Yu, Nan; Farrell, Laura
This study examined 16 years of newspapers' presentation of a prominent health issue, autism spectrum disorder (ASD). The presence of attribution of autism and stigma cues in national and local newspapers were particularly focused on. Our results illuminated intriguing trends regarding how newspapers have framed the attribution of autism and how various stigma cues have been chosen by national and local newspapers to identify autistic individuals over time. We suggest that given the evolving medical findings of autism, journalists should be alert to the changing, complex nature of this disability.